Mechanical ventilator as source of cross-infection: implications for the nursing team - Santos, Marquiony Marques dos; Alcântara, Izabel Calixa de; Bonfada, Diego; Lucena, Eudes Euler de Souza; Holanda, Cristyanne Samara Miranda de (Revista de Enfermagem UFPE on line, 2011)
ABSTRACT Objective: to identify the presence of pathogenic bacteria in the annexes of the mechanical ventilator (MV) before and after its assembly, and discuss the decontamination accomplished by the nursing team of a regional hospital. Method: this is a cross-sectional study, with an exploratory descriptive design and a quantitative nature. The data collection was carried out with swabs in five specific points of the internal parts of the annexes of mechanical ventilation, before and after its assembly, in an intensive care unit. The material collected was seeded in culture media for microorganisms of medical importance and identified at the level of genus and species through biochemical tests. The results were analyzed through the software SPSS 17.0. Results: before the assembly of the MV annexes, there was presence of 250 UFC/mm³ of Staphylococcus aureus; after the assembly of the MV annexes, 500 UFC/mm³ of Staphylococcus aureus, 250 UFC/mm³ of Enterococcus sp., and 1,000 UFC/mm³ of Enterobacter sp. were calculated. Conclusion: there were errors in the disinfection process, as well as in the manipulation of the MV annexes, presenting contamination in both moments under study. Measures of continued education for health staff, particularly for nursing team, can reduce levels of cross-infections caused by contaminated equipment. Descriptors: cross-infection; ventilators, mechanical; microbiological analysis; nursing, team; intensive care unit. RESUMO Objetivo: identificar a presença de bactérias patogênicas nos anexos do ventilador mecânico (VM), antes e após sua montagem, e discutir a descontaminação realizada pela equipe de enfermagem de um hospital regional. Método: trata-se de estudo transversal, do tipo descritivo exploratório, de natureza quantitativa. A coleta de dados foi realizada com swabs em cinco pontos específicos das partes internas dos anexos de ventilação mecânica, antes e após sua montagem, em uma unidade de terapia intensiva. O material coletado foi semeado em meios de cultura para microrganismos de importância médica e identificados em nível de gênero e espécie através de provas bioquímicas. Os resultados foram analisados com o programa SPSS 17.0. Resultados: antes da montagem dos anexos do VM, houve presença de 250 UFC/mm³ de Staphylococcus aureus; após a montagem dos anexos do VM, contabilizou-se 500 UFC/mm³ de Staphylococcus aureus, 250 UFC/mm³ de Enterococcus sp. e 1.000 UFC/mm³ de Enterobacter sp. Conclusão: houve falhas no processo de desinfecção, e, também, na manipulação dos anexos do VM, apresentando contaminação nos dois momentos estudados. Medidas de educação continuada para equipe de saúde, em especial para equipe de enfermagem, podem reduzir os índices de infecções hospitalares causadas por equipamentos contaminados. Descritores: infecção hospitalar; ventiladores mecânicos; análise microbiológica; equipe de enfermagem; unidade de terapia intensiva. RESUMEN Objetivo: identificar la presencia de bacterias patogénicas en los accesorios del ventilador mecánico (VM) antes y después de su montaje, y discutir la descontaminación realizada por el equipo de enfermería de un hospital regional. Método: esto es un estudio transversal, descriptivo exploratorio, de naturaleza cuantitativa. La recogida de datos fue realizada con swabs en cinco puntos específicos de las partes internas de los accesorios de ventilación mecánica, antes y después de su montaje, en una unidad de terapia intensiva. El material recogido fue depositado en medios de cultura para microorganismos con importancia médica y identificados a nivel de género y especie a través de pruebas bioquímicas. Los resultados fueron analizados con el programa SPSS 17.0. Resultados: antes del montaje de los accesorios del VM, hubo presencia de 250 UFC/mm³ de Staphylococcus aureus; después del montaje de los accesorios del VM, se contó 500 UFC/mm³ de Staphylococcus aureus, 250 UFC/mm³ de Enterococcus sp. y 1.000 UFC/mm³ de Enterobacter sp. Conclusión: hubo fallas en el proceso de desinfección, y, también, en el manejo de los accesorios del VM, presentando contaminación en los dos momentos estudiados. Medidas de educación continuada para el personal de salud, en especial para el equipo de enfermería, pueden reducir los índices de infecciones hospitalarias causadas por equipamientos contaminados. Descriptores: infección hospitalaria; ventiladores mecánicos; análisis microbiológico; equipo de enfermería; unidad de terapia intensiva.